Uses and nutritional value of indigenous vegetables consumed as traditional foods in Lesotho - Lephole, M. M. (University of the Free State, 2004)
A study was conducted on the usage and nutritional value of indigenous green leafy vegetables of Lesotho. Three rural areas were targeted in the districts of Mohales’ Hoek, Maseru and Leribe, which respectively represent the geographical zones mountains/highlands, lowlands and foothills. Questionnaires were used to gather information from the indigenous knowledge of the Basotho people. It was found that the plants used as leafy green vegetables were well known, mainly by the older people, and that only 5.3% of the people under study never consume them. These represented the younger people and those that would or could not face the burden of collecting them. Of the people that do consume these, 22.6% use them daily. Different traditional and common recipes were used by the people for the preparation of the indigenous vegetables, usually as a stew. A single vegetable type, or up to five different ones, were used, either to complement volume or taste. Preliminary studies on the nutritional value of the most frequently consumed vegetable types in the Maseru district showed high values, however, it was found that optimum harvest quality is of importance. Subsequently vegetables were harvested at all three the study sites and at the optimum harvest time for each. These plants were Amaranthus hybridus, Chenopodium album, Lipidium capense, Nasturtium officinale, Rorippa nudiscula, Sisymbrium capense, Sonchus dregeanus, Sonchus nanus, Urtica dioca, and Wahlengergia androsacea. An interaction was found between the vegetable type and location for all the nutrients analysed, which means that the nutritional value of all vegetables do not perform the same at the different locations. Vegetables that had an outstanding nutritional value regarding protein, lipid, vitamin C, β-carotene and mineral content are: Chenopodium album, Urtica dioca, Sisymbrium capense, Amaranthus hybridus and Rorippa nudiscula. Considering the popularity of use, nutritional value and biomass production, Chenopodium album and Amaranthus hybridus would be good candidates for development as new cash crops. Although Rorippa nudiscula is a small flat plant and will lack in biomass production, its popularity and nutritional value would also merit its development as cash crop.
Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2004
Keywords: Indigenous crops -- Lesotho; Cooking, African; Food -- Analysis